Heat stress on the feed consumption, biochemical indicators, production and milk quality of holstein and jersey cows - Adriana Hauser; Marciél França; Rainer Hauser; Laiz Perazzoli; Bruna Paula Bergamaschi Mendes; Izabelly Perdoncini Telles; Tatiane Camacho Mendes; Luiz Cláudio Miletti; André Thaler Neto (Ciência Rural)
ABSTRACT: This research compared dry matter intake, milk yield, milk composition, and physiological and biochemical parameters between holstein and jersey cows under heat stress. Holstein (n=8) and Jersey (n=8) cows were allocated into two treatment groups: VA, with cooling, and SVA, with no cooling. The experiment included 14 days of adaptation (all the cows were cooled) and 5 days of evaluation (only the VA cows were cooled). Dry matter intake and milk production were measured daily. On Day 0 of the adaptation period and on Days 1, 3 and 5 of the evaluation period, milk samples were collected for composition, physicochemical and somatic cell analysis; blood was collected for analysis of the contents of total proteins, albumin, urea, creatinine, glucose, and beta-hydroxybutyrate. The physiological parameters measured were respiratory rate, surface temperature, rectal temperature and ruminal movements. The experimental design was a 2 × 3 factorial, with two treatments and three days. The data were subjected to ANOVA and tested for normality of the residuals. For dry matter intake, there was a treatment*day interaction, and the milk yield and composition of the treatments were similar. Only the protein content was greater in the VA treatment group than in the SVA group. The milk from SVA cows had greater resistance to ethanol than that from VA cows. The freezing point was greater in the VA treatment group. The concentration of beta-hydroxybutyrate was greater in the VA treatment group. A short heat stress period did not immediately affect production, but it did affect the composition and physicochemical properties of milk. The active cooling of cows with ventilation and sprinkling influences the amount of heat produced and retained, impacting the physiological parameters, blood metabolites, composition, and physicochemical properties of milk.